2015
DOI: 10.1038/ni.3230
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-specific protease USP8 is critical for the development and homeostasis of T cells

Abstract: The modification of proteins by ubiquitin has a major role in cells of the immune system and is counteracted by various deubiquitinating enzymes (DUBs) with poorly defined functions. Here we identified the ubiquitin-specific protease USP8 as a regulatory component of the T cell antigen receptor (TCR) signalosome that interacted with the adaptor Gads and the regulatory molecule 14-3-3 . Caspasedependent processing of USP8 occurred after stimulation of the TCR. T cell-specific deletion of USP8 in mice revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 50 publications
1
62
0
Order By: Relevance
“…Dufner et al found that USP8 was essential in T cell maturation and homeostasis, although it was not required for negative selection [81]. Inhibiting USP8 leads to decrease in IL-7ra mRNA as well as Ccr7 [81].…”
Section: Usp8mentioning
confidence: 99%
“…Dufner et al found that USP8 was essential in T cell maturation and homeostasis, although it was not required for negative selection [81]. Inhibiting USP8 leads to decrease in IL-7ra mRNA as well as Ccr7 [81].…”
Section: Usp8mentioning
confidence: 99%
“…Disease mutants result in tUSP8 that now promotes EGFR recycling to the plasma membrane, instead of downregulating the receptor. Interestingly, USP8 is also cleaved in a caspase-dependent manner in T cells following TCR activation (Dufner et al, 2015).…”
Section: Regulation Of Dub Function By Proteolytic Processingmentioning
confidence: 99%
“…2 We now identified ubiquitinspecific protease 8 (USP8) as a novel component of the T cell receptor (TCR) signalosome that interacts with the adapter molecule Gads and the regulatory protein 14-3-3b. 3 Gads is highly abundant in T cells and modulates signal diversification. 4 As typical for 14-3-3 proteins, the interaction with 14-3-3b was dependent on a serine phosphorylation motif within the 14-3-3 binding motif (14-3-3BM) of USP8 (Fig.…”
mentioning
confidence: 99%
“…6 Similar to the USP8 variants found in CD patients, we identified rapid processing of USP8 in murine T cells upon activation of the TCR. 3 This processing was caspase-dependent and resulted in the generation of mouse USP8 fragments that were homologous to the fragments of the human USP8 variants found in corticotropinomas. These findings confirmed that murine and human USP8 are both proteolytically cleaved.…”
mentioning
confidence: 99%
See 1 more Smart Citation